Effects of Eh and pH on the oleate flotation of iron oxides. (November 2015) - Joseph-Soly, Sophia; Quast, Keith; Connor, Jason N.
Highlights: Many published articles relating to the effect of pH on oleate flotation of iron oxides. Very few examine the effects of Eh as well as pH. Low pH and low Eh are detrimental to the oleate flotation of iron oxides. Iron oxide flotation corresponds to region of ferric oleate stability. Abstract: Most articles published on the flotation of iron oxide minerals with oleate involve the effects of pH on the interfacial properties of the iron oxides as a function of pH, together with some attention given to the solution chemistry of the collector. It was the purpose of this study to examine what effects changing the electrochemical potential of the solution, as well as changing the pH, had on the flotation kinetics and recovery of three iron oxide minerals using sodium oleate. The results of this study confirmed the importance of the stability of ferric oleate on the surface of iron oxide minerals as a significant requirement for their flotation. The iron oxide minerals used were hematite, magnetite and goethite. Flotation kinetics could readily be simulated using a first order model, allowing the prediction of first order rate constants and ultimate recoveries. Values of these parameters were consistent with the region of stability of the ferric oleate on an Eh vs. pH equilibrium diagram for aqueous ferric oleate. Flotation of iron oxides in the acidic pH region was postulated to be promoted by the adsorption of insoluble or colloidal oleate species.